Constructing prosumer coalitions for energy cost savings using cooperative game theory - Han, L; Morstyn, T; McCulloch, M (IEEE, 2018)
Distributed energy storage (ES) is widely regarded as a tool to mitigate the supply-demand imbalance caused by intermittent generations and variable loads in a distribution network. Because a retail supplier generally offers a lower electricity sell price (e.g. feed-in tariff) than its buy price, ES owners are monetarily incentivized to store excess generation for later usage. However, since each ES owner typically optimizes the ES operation based on their individual usage profile, the joint load balancing effect of multiple ES systems becomes insignificant. This paper proposes an energy coalition, in which ES system owners operate collaboratively to minimize the total coalitional energy cost. Using cooperative game theory, the nucleolus and Shapley value are developed as methods to reward players. Finally, selected case studies compare the load balancing effectiveness of noncooperative and cooperative ES operations, and empirically demonstrate the nucleolus's stablizing characteristic, which incentivizes prosumers to stay within the grand coalition.